Basic chloroplast characterizations of Prunus campanulata x kanzakura 'praecox', a warm-adapted cherry cultivar in South China (Rosaceae). Issue 2 (3rd July 2019) - Zhou, Yuzhen; Chen, Bin; Zheng, Yan; Wei, Ziling; Zhao, Kai
Abstract: Flowering cherries are domesticated to cultivars by multiple hybridization from some original species, and there formed various adaptive abilities. Herein, we established the complete chloroplast genome of Prunus campanulata x kanzakura 'Praecox'. The chloroplast genome circle (157, 917 bp) presented a typical structure of one 85, 928 bp LSC, one 19, 117 bp SSC region, and two 26, 436 bp IRs. It encoded 124 genes, and same conserved tRNA genes and rRNA genes with P. campanulata, 37 and 8, respectively. The overall GC content was 36.72%. Phylogenetic analysis confirmed the maternal inheritance relationship that P. campanulata x kanzakura 'Praecox' comes from Prunus campanulate with little chloroplast genome change, nested inside subgenus Cerasus . This announcement of chloroplast genome would provide helps in further genetic modification and distinction mark study in Prunus genus.